For You, Forever (The Inn at Sunset Harbor-Book 7) - Sophie, Love (Lukeman Literary, 2017)
"Sophie Love's ability to impart magic to her readers is exquisitely wrought in powerfully evocative phrases and descriptions....This is the perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (Diane Donovan re For Now and Forever) FOR YOU, FOREVER is book #7 in the #1 bestselling romance series THE INN AT SUNSET HARBOR, which begins with For Now and Forever (book #1)-a free download! Fall has arrived in Sunset Harbor, and as the town clears out, Emily Mitchell enters her second trimester. Their new rooms at Trevor's house open for their first guests, while their new spa and restaurant open for business. All the while, they pursue their bid on the island, hoping to add yet another dimension to their life at Sunset Harbor. Amy insists on throwing Emily a layette in New York City, and Emily returns to her old home, in shock at how much she has changed-and at the unwanted guests who show up. She is mortified to learn that there will be a new resident of Sunset Harbor-a NYC developer who will open a rival inn-and destroy Emily's business. Chantelle goes back to school, but her new grade is an unpleasant surprise, and as things don't work out, the drama puts her into a tailspin. Roy is getting sicker, and as the weather turns cold, he invites them all to a getaway in his home in Greece, and Emily, although worried for her growing baby, cannot refuse. It is a trip that will change all of them forever, culminating in a Thanksgiving none of them will forget. FOR YOU, FOREVER is book #7 in a dazzling new romance series that will make you laugh, cry, keep you turning pages late into the night-and make you fall in love with romance all over again. Book #8 will be available soon. Sophie's new romance series, LOVE LIKE THIS, is now also available! "A very well written novel, describing the struggle of a woman (Emily) to find her true identity. The author did an amazing job with the creation of the characters and her description of the environment. The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews, Roberto Mattos (re For Now and Forever)
Keywords: Romantika, romány pro ženy